FAKTOR RESIKO SANITAS LINGKUNGAN RUMAH TERHADAP KEJADIAN CACINGAN PADA ANAK KELOMPOK KASUS DI PUSKESMAS BARA-BARAYA MAKASSAR - rosita rosita; Askar (Jurnal Ilmiah Keperawatan dan Kebidanan Holistic Care, 2019)
The incidence of worms is found in almost all parts of the world, especially in countries with tropical climates. Indonesia as a country with a tropical climate, the incidence of worms is still a public health problem with a very high prevalence of helminthiasis, especially among the less fortunate who have a high risk of contracting Soil Transmitted Helminths. The purpose of this study was to determine the relationship between sanitation factors in the home environment and the incidence of worms in the work environment of the Bara-Baraya Health Center Makassar. This study uses a case control study design with a sample of 26 respondents. The results showed that of the 26 respondents studied, there were risk factors in the control group and the case group. From the results of the chi squre test in the control group with a p value = 0.000 (incidence of worms with clean water facilities), 0.002 (incidence of worms with latrine conditions), 0.012 (incidence of worms with SPAL conditions), 0.019 (incidence of worms with conditions of house floor), 0.009 (incidence of worms with garbage disposal), and in the case group with a p value = 0.005 (incidence of worms with facilities clean water), 0.000 (incidence of worms with latrine conditions), 0.000 (incidence of worms with SPAL conditions), 0.023 (incidence of worms with conditions on the floor of the house), 0.002 (incidence of worms with landfills) p value is less than alpha = 0.05 (p value = ?). This means that H0 is rejected and Ha is accepted, so it can be concluded that there are risk factors for environmental sanitation in the home environment